Hubungan disfungsi ereksi pada pasien dislipidemia dengan lama pengobatan statin di Puskesmas Denpasar Barat I - Anak Agung Gde Ryantha Indra Pranamartha; I Gusti Ngurah Pramesemara; Yukhi Kurniawan Kurniawan (Intisari Sains Medis, 2021)
Introduction: There has been change in people's lifestyles that affect disease patterns, and dyslipidemia is one of those disease. Statins are the main pharmacological therapy for dyslipidemia. Many studies have researched the relationship between statin therapy in dyslipidemia and erectile dysfunction. However, existing research has not specifically explained this relationship.Objective: This study aims to determine the relationship between erectile dysfunction in dyslipidemic patients and duration of statin treatment at Community Health Center I West Denpasar.Methods: This research is analytic observational with cross sectional design. The study was conducted on dyslipidemic patients who took statins and met inclusion and exclusion criteria at Community Health Center I West Denpasar in May-June 2021. The sample size was 35. Duration of statin consumption was obtained through medical records and reconfirmed through questionnaire. Erectile dysfunction was measured by IIEF-5 questionnaire. Data analysis using SPSS version 21 with chi square test and Cramer's V correlation test.Results: The prevalence of erectile dysfunction in dyslipidemic patients with statin treatment at Community Health Center I West Denpasar was 85.7% with majority of the patients experiencing mild erectile dysfunction (37.1%) and taking statins for less than 12 months (51.4%). Characteristics of the patients were mostly aged 45-60 years (74.2%), obesity I (42.8%), smoking (60%), and drinking alcohol (57%). Statistical tests showed significant relationship between erectile dysfunction in dyslipidemic patients and duration of statin treatment at Community Health Center I West Denpasar  (p=0.031) with moderate correlation (r=0.552). Statins with treatment duration >12 months had protective effect against erectile dysfunction (RR = 0.81).Conclusion: There is a relationship between erectile dysfunction in dyslipidemic patients and duration of statin treatment with moderate correlation. Statins with duration of treatment >12 months have protective effect toward erectile dysfunction. Pendahuluan: Terdapat perubahan gaya hidup masyarakat yang dapat memengaruhi pola penyakit pada manusia, dimana dislipidemia adalah salah satu penyakit tersebut. Statin merupakan salah satu terapi utama untuk dislipidemia. Terdapat banyak penelitian yang telah meneliti hubungan antara terapi statin pada dislipidemia dan disfungsi ereksi. Namun, penelitian yang ada belum secara spesifik menjelaskan hubungan ini. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan disfungsi ereksi pada pasien dislipidemia dengan lama pengobatan statin di Puskesmas Denpasar Barat I.Metode: Penelitian ini adalah penelitian analitik observasional dengan desain cross-sectional. Penelitian dilakukan pada pasien dislipidemia yang mengonsumsu statin dan memenuhi kriteria inklusi dan eksklusi di Puskesmas Denpasar Barat I pada bulan Mei sampai Juni 2021. Sampel pada penelitian ini adalah 35 orang. Durasi konsumsi statin diperoleh melalui rekam medis dan dikonfirmasi ulang melalui kuisioner. Disfungsi ereksi diukur dengan kuisioner IIEF-5. Analisis data menggunakan SPSS versi 21 dengan uji chi-square dan uji korelasi Cramer’s V.  Hasil: Prevalensi disfungsi ereksi pada pasien dislipidemia dengan pengobatan statin di Puskesmas Denpasar Barat I sebesar 85,7% dengan mayoritas pasien mengalami disfungsi ereksi ringan (37,1%) dan mengonsumsi statin kurang dari 12 bulan (51,4%). Karakteristik pasien sebagian besar berusia 45-60 tahun (74,2%), dengan obesitas I (42,8%), merokok (60%), dan minum alkohol (57%). Hasil uji statistic menunjukkan hubungan yang bermakna antara disfungsi ereksi pada pasien dislipidemia dengan lama pengobatan statin di Puskesmas Denpasar Barat I (p=0,031) dengan korelasi sedang (r=0,552). Statin dengan lama pengobatan lebih dari 12 bulan memiliki efek protektif terhadap disfungsi ereksi (RR = 0,81).Kesimpulan: Terdapat hubungan antara disfungsi ereksi pada pasien dislipidemia dan lama pengobatan statin dengan korelasi sedang. Pengobatan statin dengan lama pengobatan lebih dari 12 bulan memiliki efek protektif terhadap disfungsi ereksi.